Patterns of occupational commitment among nurses: a latent profile analysis - Lin, Zihan; Wu, Wenbin; Zhang, Huifang; He, Zhiqiang; Han, Mengyu; Li, Jin (Frontiers in Psychology, 2024)
Background: Occupational commitment (OC) is a multidimensional construct that predicts turnover intentions. The interindividual variability of nurses' OC merits further exploration. Therefore, this study aims to examine patterns of OC and its relationship with psychological empowerment and job crafting in nurses.Methods: A sample of 1061 nurses was recruited from February 2022 to April 2022 by using a stratified four-stage cluster sampling procedure. A self-report survey included the Psychological Empowerment Scale, Job Crafting Scale, and Occupational Commitment Scale. Latent profile analysis (LPA) was used to examine the patterns of OC. Associations of the latent class membership with individual characteristics, psychological empowerment and job crafting were examined using multinomial logistic regression.Results: Three patterns of OC were identified: (1) "Low OC group" (n=224, 21.1%); (2) "Moderate OC group" (n=665, 62.7%); (3) "High OC group" (n=172, 16.2%). Nurses with higher education, fewer years of service, working in medicine, lower psychological empowerment and lower job crafting had a higher likelihood of belonging to Class 1 (Low OC group). In contrast, nurses working in emergency and with higher psychological empowerment and job crafting were more likely to belong to Class 3 (High OC group).The findings revealed the heterogeneity of occupational commitment among nurses in China and could guide the identification and early intervention of nurses with low level of occupational commitment.